Trading for dummies - Griffis, Michael (--For dummies., 2009)
Now updated -- your guide to trading success regardless of the market!. Want to make smarter trading decisions? This strategy-packed, no-nonsense guide presents a proven system for analyzing stocks, trends, and indicators and setting a buy-and-sell range beforehand to decrease your risk in both up and down markets. You'll discover the benefits of position trading, conduct technical analysis, and research your entry and exit points before you even purchase your stock.: Build your trading toolbox -- know the markets and exchanges, find a broker, set up your brokerage account, and determine your co.